Entrepreneurship education: The effects of challenge-based learning on the entrepreneurial mindset of university students - Alessandra Colombelli; Shiva Loccisano; Andrea Panelli; Orazio Antonino Maria Pennisi; Francesco Serraino (Administrative Sciences, 2022)
The aim of this paper is to investigate the implications of Challenge-Based Learning programs on entrepreneurial skills, and on the mindset and intentions of university students, through a quantitative approach. Resorting to an original database, we analyzed the pre- and post-levels of entrepreneurial skills, mindset and intention of 127 students who attended a Challenge-Based Learning program. Results show a positive and significant effect of Challenge-Based Learning programs on the entrepreneurial mindset and skills - that is, financial literacy, creativity, and planning - of the students.
Keywords: 350; Challenge-Based learning; EE; entrepreneurial intention; entrepreneurial mindset; entrepreneurial skills; entrepreneurship education; student entrepreneurship